An analysis of HER2 amplification in cervical adenocarcinoma: correlation with clinical outcomes and the International Endocervical Adenocarcinoma Criteria and Classification. (22nd October 2020) - Shi, Haiyan; Shao, Ying; Lu, Weiguo; Lu, Bingjian
Abstract: Few studies have explored HER2 status in cervical adenocarcinoma, particularly in the gastric‐type adenocarcinoma (GAC), a nonhuman‐papillomavirus‐related subtype with poor clinical outcomes. In this study, we investigated HER2 expression and amplification by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) in 209 well annotated cervical adenocarcinomas diagnosed using the International Endocervical Adenocarcinoma Criteria and Classification. IHC identified HER2 protein expression in 57.4% (123/209) of adenocarcinomas, of which 62 were IHC 1+ (negative), 38 2+ (equivocal) and 23 3+ (positive). HER2 amplification was found in 13 cases (6.2%) including 10 with IHC 3+ and 3 with IHC 2+. Among all the major histotypes of cervical adenocarcinoma, HER2 amplification was most common in GAC cases with a frequency of 14.7% (5/34). Moreover, HER2 amplification was more frequently associated with 2018 International Federation of Gynecology & Obstetrics (FIGO) stage III/IV, perineural involvement and ovarian spread ( p  < 0.05) while IHC 3+ was more common in patients with lymphovascular invasion and ovarian involvement ( p  < 0.05). Survival analysis indicated that FIGO stage III/IV, GAC, and p53 overexpression were associated with poor disease‐specific survival and tumor recurrence ( p  < 0.05). In conclusion, HER2 amplification was present in a subset of adenocarcinomas, and more common in GAC, pointing to a potential benefit from trastuzumab treatment. HER2 overexpression does not identify gene amplification status in cervical adenocarcinoma; therefore, FISH is suggested for both IHC positive and equivocal cases. Further investigation on more cases with longer follow‐up times is required to consolidate these findings.